Searches for Dark Matter with Superheated Liquid Techniques - A. Pullia (Advances in High Energy Physics)
This is a short review of the detectors based on the superheated liquid techniques, including continuously sensitive bubble chambers, superheated droplet detectors (SDD) and Geysers.